The imperatives of NDE programs for poverty reduction and youth employment in Nigeria - Musa, Umar Farouk; Abdullah, Mohamad Ainuddin Iskandar Lee; Wahid, Ratnaria (2016)
The constitutional roles of National Directorate of Employment NDE on job creation and implications for poverty reduction have accelerated economic development via its laudable initiatives of establishing 174 skills acquisition centers in the thirty six states of Nigeria and the Federal capital Territory, Abuja.Concurrently, four model centers were equipped with boarding facilities and accommodated trainees.A total of 1721 participants of the Rural Agricultural Development Scheme were trained in different apprentice programs in 2014 alone despite its political and organizational challenges.This study uses qualitative research design, non-probability sampling, and semi structured interview via fifteen informants; we analyzed the data with Nvivo software.Our cardinal objectives were to explore the employment generation strategies and poverty reduction initiatives of this Directorate.Findings from our study reveal that the four basic packages of Small Scale Enterprises, Vocational Skills Development, Rural promotion scheme and Special Public Works were the prominent capacity building programs undertaken by this institution since its establishment in last 30 years.Our study passionately, recommended for the Provision of social amenities such constant electricity supply, funding and establishment of modern equipments, diversification of the economy, Good Governance and proper management of the endowed resources and establishment agro-entrepreneurship/ agribusiness projects respectively.